Assessment on technological constraints of State management in Ha Nam Province following the national standards ISO 9001:2000 - Tien, Nguyen Manh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
State administrative management in Vietnam has been step by step reformed and regularly evaluated in line with the state organizational machinery. A new form of management being applied is to follow the national standards ISO 9001:2000; it is actually a set of International Standards applicable to Vietnam, in nature, on the other hand, it is a technology. Since 2007, Ha Nam province and other provinces in the country have applied the ISO 9001:2000 in the field of state administrative management. Like other provinces, Ha Nam has encountered many conflicting matters that should be analyzed and studied with a view to improve the policies accordingly. This paper presents an assessment on technological constraints in applying the national standards ISO 9001:2000 in state administrative management in Ha Nam province and proposes solutions for further improvement in the application of such standards. Code: 13082701 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">